Incidence, Healthcare Resource Use and Costs Associated With Incisional Hernia Repair - Laurie Smith; Emily Wilkes; Chris Rolfe; Petra Westlake; Julie Cornish; Paul Brooks; Jared Torkington (Journal of Abdominal Wall Surgery, 2024)
Background: Incisional hernia (IH) is a common complication of abdominal surgery affecting between 12.8% and 30% of patients. In spite of this, rates of IH repair remain low, at around 5% in the literature. We aimed to assess the rate of IH repair in the UK across surgical specialties and the cost burden associated with IH repair.Methods: This is a retrospective observational study of patients undergoing abdominal surgery in England between 2012 and 2022 using the Hospital Episode Statistics (HES) database. Index abdominal surgery was identified between March 2014 and March 2017. Diagnostic and surgical procedure codes were used to identify pre-operative risk factors, index surgeries, IH repair and healthcare contact. Healthcare resource use (HCRU) costs were derived for index surgery and all post-index, non-elective inpatient admissions and outpatient visits using Healthcare Resource Group (HRG) codes within HES.Results: Of 297,134 patients undergoing abdominal surgery, 5.1% (n = 15,138) subsequently underwent incisional hernia repair. By specialty, rates were higher in Colorectal (10.0%), followed by Hepatobiliary (8.2%), Transplant (6.8%), Urological (4.0%), Bariatric (3.5%), Vascular (3.2%) and Gynaecological (2.6%) surgery. Patients undergoing IH repair had more healthcare contacts, longer length of inpatient stays and more A+E visits vs. those with no IH repair post index surgery (83% ≥ 1 A+E visit vs. 69%), as well as higher rates of referral to mental health services (19.8% vs. 11.5%). IH repair was associated with an average HCRU cost of £23,148 compared to £12,321 in patients with no IH repair.Conclusion: Patients undergoing IH repair have a greater morbidity than those not undergoing repair, shown by higher HCRU and more healthcare contacts. Despite this, rates of surgery for IH are low, suggesting that most patients with hernias are not undergoing repair. Emphasis must be placed squarely on primary prevention, rather than cure.